INTEGRATED «ACADEMIC MASTER'S - PHD» EDUCATIONAL PROGRAMS - Boris I. Bednyi; Oleg A. Kuzenkov (Высшее образование в России, 2016)
We propose the concept of integrating programs of the second and third levels of higher education and creating exclusive educational systems «Academic Master's program - postgraduate school» on this basis. The purpose of such systems is to provide systematic targeted training of highly qualified experts (holders of Candidate of Sciences degree) for professional research and teaching work in higher education institutions. The programs are focused on a small number of Bachelor program graduates, who are motivated and possess cognitive and psychological qualities that allow them to prefer an academic career, given the minimum necessary conditions. We consider some organizational, structural and content features of the integrated programs, including the institutional integration of Master's and postgraduate program levels, as well as a number of issues related to the focused step-by-step development of research and teaching competencies throughout the whole «path» of preparation for the Candidate of Sciences degree. A modular structure of the educational component of the program is proposed. By using an example of the program in the area of studies «Computer Science and Computer Engineering », a curriculum option is discussed.